The Effects of E-Performance and Digital Leadership on Self-Motivation and Employee Performance in MSMEs - Lahumuddin, Muhammad Yasin Parawangsa; Rahmad Solling Hamid; Qamaruddin, Muhammad Yusuf (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. This study aims to determine the role of e-performance and digital leadership in enhancing self-motivation and employee performance in micro, small, and medium enterprises (MSMEs) in North Luwu. The study employs a quantitative approach targeting all employees involved in MSMEs in North Luwu as the research population. Empirical analysis was conducted using a sample of 309 millennials. Data collection was carried out through an online survey. After passing reliability and validity tests, the data were analyzed using a structural equation model based on partial least squares (PLS-SEM). The research results indicate that e-performance has a significant and positive direct impact on employee performance (0.001 < 0.005) and self-motivation (0.000 < 0.05). Similarly, digital leadership shows a significant and positive direct effect on employee performance (0.002 < 0.05) and self-motivation (0.000 < 0.05). Interestingly, however, self-motivation does not have a positive direct impact on employee performance (0.127 > 0.05), thus rejecting one of the five hypotheses proposed in this study. This research can contribute to managers and employees of MSMEs regarding the importance of implementing an effective e-performance system and digital leadership to improve MSME employee performance and motivation. Managers must ensure that the e-performance system provides constructive feedback and focuses on key elements such as accessibility and accuracy. Furthermore, digital leadership needs to support the development of technological skills and an innovation-driven culture. The findings of this study can also provide empirical support for the theory of planned behavior, thus providing a more comprehensive model of the relationship between e-performance, digital leadership, self-motivation, and employee performance. Keywords: E peformance, digital leadership, self-motivation, employee performance, and MSMEs Abstrak. Penelitian ini bertujuan untuk menentukan peran e-performance dan kepemimpinan digital dalam meningkatkan motivasi diri dan kinerja karyawan pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Luwu Utara. Studi ini menggunakan pendekatan kuantitatif dengan sasaran seluruh karyawan yang terlibat dalam UMKM di Luwu Utara sebagai populasi penelitian. Analisis empiris dilakukan dengan menggunakan sampel sebanyak 309 generasi milenial. Pengumpulan data dilakukan melalui survei online. Setelah data lolos uji reliabilitas dan validitas, data dianalisis dengan model persamaan struktural berbasis partial least squares (PLS-SEM). Hasil penelitian menunjukkan bahwa e-performance berpengaruh signifikan dan positif secara langsung terhadap kinerja karyawan (0.001 < 0.005) dan motivasi diri (0.000 < 0.05). Demikian pula, kepemimpinan digital menunjukkan efek signifikan dan positif secara langsung terhadap kinerja karyawan (0.002 < 0.05) dan motivasi diri (0.000 < 0.05). Namun, menariknya, motivasi diri tidak berpengaruh positif secara langsung terhadap kinerja karyawan (0.127 > 0.05), sehingga menolak salah satu dari lima hipotesis yang diajukan dalam penelitian ini. Penelitian ini dapat memberikan kontribusi bagi manajer dan karyawan UMKM mengenai pentingnya penerapan sistem e-performance yang efektif dan kepemimpinan digital untuk meningkatkan kinerja dan motivasi karyawan UMKM. Manajer harus memastikan bahwa sistem e-performance memberikan umpan balik konstruktif dan fokus pada elemen-elemen kunci seperti aksesibilitas dan akurasi. Selain itu, kepemimpinan digital perlu mendukung pengembangan keterampilan teknologi dan budaya inovasi. Temuan penelitian ini juga dapat memberikan dukungan empiris untuk teori perilaku terencana, sehingga menyediakan model yang lebih komprehensif tentang hubungan antara e-performance, kepemimpinan digital, motivasi diri, dan kinerja karyawan. Kata kunci: E peformance, digital leadership, motivasi diri, kinerja karayawan, and UMKM